Comparative Structures and Evolution of Vertebrate Carboxyl Ester Lipase (CEL) Genes and Proteins with a Major Role in Reverse Cholesterol Transport. (20th November 2011) - Holmes, Roger S.; Cox, Laura A.
Abstract : Bile-salt activated carboxylic ester lipase (CEL) is a major triglyceride, cholesterol ester and vitamin ester hydrolytic enzyme contained within pancreatic and lactating mammary gland secretions. Bioinformatic methods were used to predict the amino acid sequences, secondary and tertiary structures and gene locations for CEL genes, and encoded proteins using data from several vertebrate genome projects. A proline-rich and O-glycosylated 11-amino acid C-terminal repeat sequence (VNTR) previously reported for human and other higher primate CEL proteins was also observed for other eutherian mammalian CEL sequences examined. In contrast, opossum CEL contained a single C-terminal copy of this sequence whereas CEL proteins from platypus, chicken, lizard, frog and several fish species lacked the VNTR sequence. Vertebrate CEL genes contained 11 coding exons. Evidence is presented for tandem duplicated CEL genes for the zebrafish genome. Vertebrate CEL protein subunits shared 53–97% sequence identities; demonstrated sequence alignments and identities for key CEL amino acid residues; and conservation of predicted secondary and tertiary structures with those previously reported for human CEL. Phylogenetic analyses demonstrated the relationships and potential evolutionary origins of the vertebrate CEL family of genes which were related to a nematode carboxylesterase ( CES ) gene and five mammalian CES gene families.